LOS DERECHOS LINGÜÍSTICOS Y LA EDUCACIÓN EN LENGUAS INDÍGENAS EN LA ENCRUCIJADA DEL DESARROLLO SOSTENIBLE - García Askoaga, Inés Maria (2020)
Linguistic diversity is part of the world’s intangible heritage. But not all languages enjoy the same status or recognition. Alongside the great majority languages, there are many indigenous and minority languages that are barely noticed, and whose speakers are deprived of some basic rights such as education in their native language. This contribution address to the interactive dimension of language as part of human activity, and the mother tongue as a speaker’s right recognized by UNESCO; then it turns the attention to the role played by linguistic diversity in the Sustainable Development Goals to underline its importance for such development; It also stress the need to foster mother-tongue-based multilingual education.